Effect of tomographic operator inaccuracies and respiratory motion on PET/CT lung nodule images smearing. Issue 2 (February 2017) - Daouk, Joël; Bailly, Pascal; Bouzerar, Roger; Meyer, Marc-Étienne
Abstract : Background: In thoracic PET/computed tomography (CT) imaging, uptake foci usually appear smeared because of postreconstruction smoothing and respiratory motion. Objective: The aim of the present study was to assess the respective contributions of the reconstruction process and respiratory motion on PET/CT images. Materials and methods: Thirty-one pulmonary lesions were studied. Free-breathing PET/CT acquisitions were followed by a 10-min respiratory-gated PET/CT acquisition. Four different reconstructions were performed by combining two different tomographic operators (TOs) (i.e. the geometric clinical system matrix or a system matrix including the detector response) and taking account (or not) of respiratory motion using a previously developed 'CT-based' technique. For each reconstruction method, lesion segmentation was performed with an adaptive threshold. Next, we computed the volume differences between each reconstruction. Finally, we applied a multiple linear model to compute the relative contributions of TO-based and CT-based respiratory compensation to lesion volume. Results: The three groups, combining the reconstruction methods and the respiratory compensation (or not), differed significantly in terms of the volume differences. For all lesions, the full linear model yielded a regression coefficient R 2 of 76.10%. The partial R 2 values were 65.58 and 10.52% for the detector response operator and the CT-based method, respectively. For lesions in the upper/middle lobes, blurring was mainly because of TO (partial R 2 =78.53%), whereas, for lower lobe lesions, smearing was mainly because of respiratory motion (partial R 2 =56.76%). Conclusion: Our results showed that image reconstruction, by TO accuracy, was the main explanatory factor for lesion smearing when considering the chest as a whole. Respiration had a major impact on the lower lobes.